PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA DI SDN SRONDOL KULON 02 SEMARANG - Pangesti Mutia Anjani; Nursiwi Nugraheni; Teguh Budi Prakoso (STKIP Subang, 2024)
ABSTRACT In the world of education, the problem currently faced is the weakness of the learning process in general. Many students experience difficulties in carrying out the learning process, resulting in low subject grades for these students. One of the factors that causes a decline in student learning outcomes is the existence of different levels of ability between one student and another. The problem to be studied in this research is whether the STAD type cooperative learning model can improve the learning outcomes of class IV students in Indonesian language subjects at SDN Srondol Kulon 02 Semarang. This research aims to improve the learning outcomes of class IV students at SDN Srondol Kulon 02 Semarang by using the STAD type cooperative learning model. This research is classroom action research with the subjects of this research being class IV students with a total of 28 people. The research results show that the learning outcomes obtained by students in cycle I, cycle II and cycle III have increased. This is evidenced by a significant increase in the level of classical completion, namely 29% in cycle I, increasing in cycle II to 75% and in cycle III increasing to 96.42%.